Effect of statins on atherogenic serum amyloid A and α1-antitrypsin low-density lipoprotein complexes. (15th December 2016) - Miyazaki, Yusuke; Katanasaka, Yasufumi; Sunagawa, Yoichi; Hirano-Sunagawa, Sae; Funamoto, Masafumi; Morimoto, Eriko; Komiyama, Maki; Shimatsu, Akira; Satoh-Asahara, Noriko; Yamakage, Hajime; Wada, Hiromichi; Hasegawa, Koji; et al.
Abstract: Purpose: HMG-CoA reductase inhibitors, also termed statins, are used to reduce the risk of coronary artery disease. Two oxidatively modified low-density lipoprotein (LDL) complexes, serum amyloid A-LDL (SAA-LDL) and α1-antitrypsin-LDL (AT-LDL), serve as atherosclerotic, inflammatory, and cardiovascular risk markers. In this study, we examined the effects of hydrophilic rosuvastatin (RSV) and lipophilic pitavastatin (PTV) on these markers in patients with hypercholesterolemia. Methods: The present study was a sub-analysis of our previous STAT-LVDF study. The subjects were treated with RSV or PTV for 24 weeks. Changes in glucose-lipid metabolism, serum levels of SAA-LDL and AT-LDL, and C-reactive protein (CRP) level were assessed. Results: In total, 53 patients were analyzed in the present study. RSV and PTV significantly decreased SAA-LDL (RSV: p  = 0.003, PTV: p  = 0.012) and AT-LDL levels (RSV: p  = 0.013, PTV: p  = 0.037). Changes in SAA-LDL level were significantly and positively correlated with those in CRP in both the RSV ( r  = 0.549, p  = 0.003) and PTV ( r  = 0.576, p  = 0.004) groups. Moreover, a positive correlation between changes of SAA-LDL levels and those of HbA1c levels was observed in the PTV group ( r  = 0.442, p  = 0.030) but not in the RSV group ( r  = − 0.100, p  = 0.611). Conclusions: Both hydrophilic rosuvastatin and lipophilic pitavastatin reduce serum levels of atherosclerotic and inflammatory markers. These findings also indicate differential effects of RSV and PTV on glucose tolerance. Highlights: Oxidatively-modified LDLs are a known cardiovascular risk marker. Both rosuvastatin and pitavastatin decreased oxidatively-modified LDL levels. In both statin groups, change in oxidatively-modified LDL level was correlated with that in CRP. In the pitavastatin group, change in HbA1c level was correlated with that in serum amyloid A-LDL level.